Corporate lobbying and accounting conservatism - Tsang, Hiu Leong (ProQuest Dissertations & Theses, 2008)
Firms engage in lobbying activities to shape and achieve their strategic goals. Using corporate lobbying spending data for the years between 2000 and 2004, I examine the association between corporate lobbying activities and accounting conservatism. Firms that lobby intensely are more likely to be subject to public and Congressional scrutiny. As such, I hypothesize and find that corporate lobbying activity is positively associated with accounting conservatism after controlling for the demand for accounting conservatism documented in prior studies; i.e., contracting, litigation, tax, and regulatory demands. In addition, I show that the positive association between lobbying and accounting conservatism is more pronounced for firms with high media exposure, firms operating in states with high levels of lobbying regulations, and firms that hire high-profile professional lobbying firms. Results of this study are consistent with the political cost hypothesis and support the argument that firms engaged in lobbying activities use accounting conservatism to mitigate political costs arising from the increased likelihood of public and Congressional scrutiny.